Geophysical survey of Neovolcanic complexes in the first protection zone of the Sliač Spa and the Baková jama - PAŠIAKOVÁ, Mariana; GAJDOŠ, Vojtech; BUČOVÁ, Jana; DÉREROVÁ, Jana; STRAKA, Adam; HLAVŇOVÁ, Petra; BRIXOVÁ, Bibiana (Contributions to Geophysics and Geodesy, 2014)
The main purpose of the survey in the 1st protection zone area of the Sliač Spa and the Bakov´a jama was to clarify the geological-tectonical structure. The vertical electric sounding (VES) technique was selected as the main geophysical survey method. Additionally, the soil radon emanometry was carried out to verify tectonic lines’ presence. The outcrop of Pre-Tertiary basement was discovered in the form of small isolated island. No tectonic line was identified based on the evaluation of profile radon concentration. The results of geoelectrical measurements are presented in 8 geological-geophysical crosssections. The results and the tectonic lines’ courses interpreted by the VES method are drawn in the map of new indications. The isoline maps and 3D model of Pre-Tertiary basement were constructed.